Regulation of Hippocampal Gamma Oscillations by Modulation of Intrinsic Neuronal Excitability - Klemz, Alexander; Wildner, Florian; Tütüncü, Ecem; Gerevich, Zoltan (Frontiers in Neural Circuits, 2022)
Ion channels activated around the subthreshold membrane potential determine the likelihood of neuronal firing in response to synaptic inputs, a process described as intrinsic neuronal excitability. Long-term plasticity of chemical synaptic transmission is traditionally considered as the main cellular mechanism of information storage in the brain, however, voltage- and calcium-activated channels modulating the inputs or outputs of the neurons are also subjects of plastic changes and play a major role in learning and memory formation. Gamma oscillations are associated with numerous higher cognitive functions such as learning and memory but our knowledge on their dependence on intrinsic plasticity is by far limited. Here we investigated the roles of potassium and calcium channels activated at near subthreshold membrane potentials in cholinergically induced persistent gamma oscillations measured in the CA3 area of rat hippocampal slices. Among potassium channels, which are responsible for the afterhyperpolarization in CA3 pyramidal cells, we found that blockers of SK (KCa2) and KV7.2/7.3 (KCNQ2/3), but not theBK (KCa1.1) and IK (KCa3.1) channels, increased the power of gamma oscillations. On the contrary, activators of these channels had an attenuating effect without affecting the frequency. Pharmacological blockade of the low voltage-activated T-type calcium channels (CaV3.1-3.3) reduced gamma power and increased the oscillation peak frequency. Enhancement of these channels also inhibited the peak power without altering the frequency of the oscillations. The presented data suggest that voltage- and calcium-activated ion channels involved in intrinsic excitability strongly regulate the power of hippocampal gamma oscillations. Targeting these channels could represent a valuable pharmacological strategy against cognitive impairment.